DAMPAK KABUT ASAP PADA KEHIDUPAN MASYARAKAT DI KELURAHAN TUAH KARYA KECAMATAN TAMPAN KOTA PEKANBARU PROVINSI RIAU (JURNAL SPASIAL, 2015)
The pollution has become a very serious problem at the present time. The problem of the haze forest firest that accur on 25 agustus 2015 in Riau can also lead air pollution in village Tuah Karya district Tampan city’s Pekanbaru occurance air pollution is also to disturb some sector such as : 1) Health society in the Kelurahan Tuah Karya district Tampan city’s Pekanbaru province. Of Riau at the haze classified as it is not good with the rate of achievement respondents of 76,07%, 2) Economic affairs society in the village Tuah Karya distrct Tampan city’s Pekanbaru Province of Riau to income per month an average of Rp 1.000.000 – Rp 1.500.000 with the rate of achievement 76,27% of respondents, 3) Enviroment society in the village Tuah Karya district Tampan city’s Pekanbaru Province of Riau as haze happened classified as it is not good where air quality that is not good for the people with the rate of achievement respondents 85,59% so, it can be taken the conclusion that the public health as haze influential on the condition of thepublic health, so many people who are sick like ISPA, coughing, allergies and irritation eyes. Not only health but smog also effect the social condition of the economi and environment residents where in come of a very plummeted an fall air quality also makes activities come disturbed.Key Word : Health, Economic and the Environment